Understanding jurisprudence : an introduction to legal theory - Wacks, Raymond (Oxford ; New York, NY ; India : Oxford University Press, 2017)
Understanding Jurisprudence provides an illuminating and engaging introduction to the central questions of legal theory. It is the perfect starting point for those new to the subject.
What's it all about? -- Natural law and morality -- Classical legal positivism -- Modern legal positivism -- Law and moral legitimacy -- Legal realism -- Law and social theory -- Historical and anthropological jurisprudence -- Theories of justice -- Rights -- Why obey the law? -- Why punish? -- Critical legal theory -- Feminist theory -- Jurisprudence understood?
Previous edition: 2015
Includes bibliographical references and index.
School of Law
Keywords: Jurisprudence; Law -- Philosophy; Law